The Use of Special Exercises in The Development of Strength Quality of Wrestlers. (Global Scientific Review, 2024)
In this article, it is explained about the effective organization of the training process with the effective use of special tools to improve the physical, technical-tactical and psychological preparation of wrestlers, to develop the quality of strength.